Overview of Dementia Elderly Care during the COVID-19 Pandemic: Literature review study - Mutia Nur Maulida Sandy; Hanny Rasni; Tantut Susanto; Latifa Aini Susumaningrum; Fahruddin Kurdi (Media Keperawatan Indonesia, 2023)
During the COVID-19 pandemic, the elderly with dementia face challenges in the form of changes in daily routines and the absence of social services, making the task of care shift completely to the family. Families who are not ready to provide appropriate and effective care will have an impact on cognitive deterioration and the development of their dementia condition. The purpose of this study was to describe the care of elderly dementia during the COVID-19 pandemic. The research design used in this study is a narrative literature review. The selection of articles is carried out through 4 stages of the PRISMA flowchart. Articles are searched through Pubmed, Springer Link, Plos One and Google Scholar. The results of the study are the findings of 10 articles that describe the care of elderly dementia during the COVID-19 pandemic in the form of home-based and clinical trial-based care. Clinical trials treatment in the form of telehealth, Mario robot, Tv-assist Dem, and a stationary bicycle, while home-based care is in the form of basic care that is not much different from pre-pandemic while still adhering to health protocols. The conclusion of this study is the need for the elderly with dementia to continue to receive care during the COVID-19 pandemic to avoid worsening cognitive function and the development of dementia which can ultimately have an impact on their health status and quality of life.